PERSEPSI MAHASISWA TERHADAP AKUN INSTAGRAM @INFOUNP SEBAGAI MEDIA INFORMASI AKADEMIK - Muhammad Fadly; Desriyeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the perceptions of students of the Department ofInformation and Library Science, Padang State University, towards the Instagramaccount @infounp as an academic information medium. This study uses aquantitative approach with a descriptive method. The data collection techniquewas carried out by distributing online questionnaires to 78 active students who arefollowers of the @infounp account, with the sample determined using the Slovinformula. The research instrument was compiled based on five indicators of theUses and Gratifications theory, namely: information needs, timeliness, clarity ofinformation, ease of access, and user satisfaction. The results showed thatstudents perceptions of the @infounp Instagram account were generally in thevery good category with an achievement score of 82.0%. From the analysis, thefindings of the average score for each indicator were as follows: information needs(4.08), timeliness (3.97), clarity of information (4.17), ease of access (4.08), anduser satisfaction (4.08). These findings indicate that the @infounp account hasplayed an effective role in conveying academic information to students, althoughthere are still notes regarding the clarity and interactivity in delivering its content.